(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The increasingly dynamic development of technology requires humans to act quickly and precisely so as not to compete with other humans. The importance of CSR activities has been supported by the government with the issuance of Law No. 40 of 2007 concerning Limited Liability Companies in Article 74 paragraph 1 concerning Social and Environmental Responsibility. This research aims to determine the public’s perception of the CSR program in Tenggarong District and to determine the impact of CSR on community welfare in Tenggarong District, Kutai Kartanegara Regency. Data methods and analysis aim to simplify all the data collected, present it systematically, and then process, interpret, and make sense of the data. This research uses qualitative analysis methods. The community around the company in Tenggarong District still has a negative perception of CSR implementation. Even though the public agrees with the CSR program, the public’s response is still poor regarding the company’s CSR program. The company has carried out social responsibility towards the surrounding community even though it has not had a big influence on the welfare of society in the economic sector because the social responsibility given is still in the form of consumptive use, in other words, once used, it runs out immediately. For the social responsibility that is currently given on a one-time basis, it would be better to provide it in the form of capital for community MSMEs.